Maternal health care utilization and neonatal mortality in Nigeria: looking beyond the micro-level pathway of influence (2017)
Neonatal mortality is a neglected but largely preventable public health challenge in Nigeria. The country contributes the largest number of neonatal deaths in Africa, and this is an important reason for the failure of the country to meet Millennium Development Goal (MDG4) of reducing child mortality. Maternal health services provide the platform for delivering cost-effective interventions that reduce maternal and child mortality. Thus, we examined the relationship between the utilization of maternal health services and neonatal mortality in Nigeria by carrying out a multilevel Cox proportional regression analysis of the most recent Nigeria Demographic and Health Survey (2013 NDHS) in order to decompose the micro and macro level factors on the pathway of influence for neonatal mortality. Hazards of neonatal death were significantly lower for children whose mothers had 4 or more antenatal visits by skilled providers (HR: 0.78, CI: 0.61-0.98, p<0.05) and whose mothers received postnatal care from skilled provider (HR: 0.41, CI: 0.30-0.56, p<0.05) even after adjusting for other control variables. There was also a significantly elevated hazards of neonatal mortality for mothers in rural areas (HR: 1.44, CI: 1.09-1.90). Our findings highlight the importance of maternal health care services for neonatal mortality reduction especially in the rural areas.